US Policy And Interests In The Current Conflicts Of The Arab Countries / Middle East / - Dayyoub, Mhd. Ma'en; Ismail, Roula; Marouf, Thayer (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The research started from the importance of Knowledge things that drive the decisions of US foreign policy in the world and the Middle East in particular, in light of the wave of unrest that swept the region under the names of many of the most important is appearance of the wars of change, which was intended to change the systems of leadership and governance in these areas, the pretext of freedom, Of the strategies (soft power, hard power, and smart power), driven by the achievement of their objectives in these areas, based on her economic interests, which is what the essence of the problem of research, the researcher found that the oil has a major strategic impact on the policies of the United States applied and tools used to implement these policies in the areas where the oil is present Basically. In addition, the relationship between the tenets of American supremacy (Oil, giant companies, the Zionist entity) which constitute the essence of its national security, is an integrative relationship, whereas the relationship between US national security and wars is a correlative correlation relationship. The wars or tensions to which America is a party, Of a way or strategy based on exporting domestic crises abroad by creating a global crisis, in order to ensure the safety of USA national security, and the continued realization of the US economic interests. انطلق البحث من ضرورة معرفة ما يحرك قرارات السياسة الخارجية الأميركية في العالم عموما ومنطقة الشرق الأوسط خصوصاً، وذلك في ظل موجة من الاضطرابات التي اجتاحت دول المنطقة تحت مسميات عديدة كان في مقدمتها ظهور حروب التغيير التي أحدثت بقصد تغيير أنظمة القيادة والحكم في هذه الدول، بحجة الحرية، معتمدة بذلك على عدة انواع من الاستراتيجيات والأدوات منها (القوة الناعمة والقوة الخشنة و القوة الذكية)، مدفوعة بتحقيق أهدافها في هذه المناطق انطلاقا من مصالحها الاقتصادية، هو ما مثل جوهر الاشكالية البحثية، وقد توصل الباحث إلى أن للنفط اثراً استراتيجياً كبيراً وهاماً في سياسات الولايات المتحدة الأميركية المتبعة، وأدواتها المستخدمة في تطبيق هذه السياسات بالمناطق التي يتواجد فيها النفط بشكل أساسي. إضافة إلى أن العلاقة بين ثوابت السياسة الأمريكية ( النفط, الشركات العملاقة, الكيان الصهيوني) التي تشكل جوهر الامن القومي للولايات المتحدة الأمريكية هي علاقة تكاملية، في حين أن العلاقة بين الأمن القومي الأمريكي والحروب واضطرابات الدول, هي علاقةُ ارتباطٍ مصلحيٍّ، فالحروب أو التوترات التي تكون الولايات المتحدة طرف فيها, هي عبارة عن أسلوب أو استراتيجية قائمة على تصدير أزماتها الداخلية نحو الخارج، لخلق أزمة عالمية, بما يضمن سلامة أمنها القومي، واستمرار تحقيق مصالحها الاقتصادية.